2011
DOI: 10.1086/658665
|View full text |Cite
|
Sign up to set email alerts
|

Role of Unit-Specific Combination Antibiograms for Improving the Selection of Appropriate Empiric Therapy for Gram-Negative Pneumonia

Abstract: In an effort to improve the selection of appropriate empiric gram-negative therapy for pneumonia, we examined intensive care unit-specific combination antibiograms. These antibiograms were able to predict appropriate empiric gram-negative therapy. Empiric combination therapy based on unit-specific combination antibiograms may aid in the selection of therapy for gram-negative pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 7 publications
2
22
0
1
Order By: Relevance
“…They concluded that reporting antibiotic susceptibility data in the form of a combination antibiogram may be useful to clinicians who are considering empirical antimicrobial therapy in the intensive care unit. A study by Pogue et al (2011) examined the susceptibility and resistance patterns of 467 gram negative ICU respiratory isolates. They found that the addition of a fluoroquinolone to an antipseudomonal beta-lactam did not substantially improve coverage, since nearly all beta-lactam resistant isolates were subsequently cross-resistant to fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that reporting antibiotic susceptibility data in the form of a combination antibiogram may be useful to clinicians who are considering empirical antimicrobial therapy in the intensive care unit. A study by Pogue et al (2011) examined the susceptibility and resistance patterns of 467 gram negative ICU respiratory isolates. They found that the addition of a fluoroquinolone to an antipseudomonal beta-lactam did not substantially improve coverage, since nearly all beta-lactam resistant isolates were subsequently cross-resistant to fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
“…To assist clinicians in selecting the most effective twodrug antibiotic regimen, combination antibiograms have been employed (Apisarnthanarak and Mundy, 2008;Christoff et al, 2010;Fox et al, 2008;Mizuta et al, 2006;Pogue et al, 2011). These antibiograms can be displayed in matrix form showing the percentage of isolates susceptible to various single agents and combinations of antibiotics.…”
Section: Ajidmentioning
confidence: 99%
“…Regardless, appropriate diagnostic and microbiological workup should be performed with rapid escalation, de-escalation and/or discontinuation when appropriate. for DAAT [53]. Combination antibiograms offer significant advantages over traditional antibiograms as they focus on susceptibility of potential second agents for combination (e.g.…”
Section: Risk Profilingmentioning
confidence: 99%
“…Furthermore, unit-specific combination antibiograms have the ability to differentiate susceptibility profiles among various units of an institution. Pogue and colleagues used this technique to identify that the most effective combination regimen in the medical intensive care unit (an anti-pseudomonal β-lactam plus amikacin) was different from that in the surgical intensive care unit (an anti-pseudomonal β-lactam plus levofloxacin) at their institution [53]. Data from Nicasio and colleagues suggest that combination antibiograms could be "taken to the next level" by including MIC distributions and pharmacodynamic dosing recommendations for ventilator associated pneumonia [54].…”
Section: Risk Profilingmentioning
confidence: 99%
“…Whereas institution-specific antibiograms serve clinicians who provide patient care in a variety of care units, unit-specific antibiograms have emerged as a useful tool for institutions with units devoted to a homogeneous patient population [6][7][8]. Unitspecific antibiograms can guide initial antibiotic choices for different populations within the same institution [7,9].…”
mentioning
confidence: 99%